Clase Magistral pronunciada por el Profesor Vincenzo Ferrari - Ferrari, Vincenzo (2014)
Speech delivered on October 6, 2014, at the Faculty of Law of the University of Buenos Aires, on the occasion of receiving the Honorary Doctorate